2019
DOI: 10.1093/gigascience/giz058
|View full text |Cite
|
Sign up to set email alerts
|

Disordered gut microbiota and alterations in metabolic patterns are associated with atrial fibrillation

Abstract: Background With the establishment of the heart-gut axis concept, accumulating studies suggest that the gut microbiome plays an important role in the pathogenesis of cardiovascular diseases. Yet, little evidence has been reported in characterizing the gut microbiota shift in atrial fibrillation. Methods We include the result of the global alterations that occur in the intestinal microbiota in a cohort of 50 patients with atrial fibrillation and 50 matched controls based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
147
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(175 citation statements)
references
References 74 publications
15
147
1
Order By: Relevance
“…In our previous research, disordered GM was shown to be associated with the development of AF [18]. Interestingly, the present study indicated an incremental prognostic accuracy over clinical predictors of the novel predictive model based on GM taxonomic profiles.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…In our previous research, disordered GM was shown to be associated with the development of AF [18]. Interestingly, the present study indicated an incremental prognostic accuracy over clinical predictors of the novel predictive model based on GM taxonomic profiles.…”
Section: Discussionsupporting
confidence: 63%
“…In the current study, we included 90 participants from our previous cohort [18], with 50 non-AF controls (CTRs) and 40 AF patients. All AF cases underwent radiofrequency catheter ablation before feces collection, and the patients remained in sinus rhythm (normal beating of the heart) until the end of the procedure, with confirmed circumferential pulmonary vein isolation (CPVI) and ablation line blockage [4].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations